Pathogenicity and molecular characterization of a GI-19 infectious bronchitis virus isolated from East China - Wu, Qi; Xu, Mengcheng; Wei, Dengle; Zhang, Xuehua; Li, Ding; Mei, Mei (Frontiers in Veterinary Science, 2024)
Infectious bronchitis virus (IBV) is the etiological agent of avian infectious bronchitis, a disease that is widespread in countries with intensive poultry farming. Multiple genotypic IBV strains are prevalent in China, and understanding the dominant genotypes of IBV in specific regions is crucial for the prevention and control of IBV. In this study, the IBV strain CK/CH/WJ/215 was isolated from a diseased commercial chicken flock in 2021 in China. The CK/CH/WJ/215 isolate was clustered together with viruses in the GI-19 lineage on the basis of complete S1 sequence analysis. According to the complete S1 sequence analysis, CK/CH/WJ/215 shares low identity (75.7%, 78.6%, and 77.5%) with the three vaccination strains, H120, LDT3-A, and 4/91. Further analysis based on the potential glycosylation of S1 showed that the isolate exhibited new glycosylation sites at positions 138 and 530 in comparison to those of the H120 and LDT-A vaccine strains, respectively. The pathological assessment revealed that the isolate was a nephropathogenic IBV strain that caused a high morbidity of 100% and a mortality of 73.3% in 7-day-old specific-pathogen-free (SPF) chicks.The CK/CH/WJ/215 isolate exhibited broader tropisms in different tissues, including the trachea, lungs, kidneys, and bursa of Fabricius. This study conducted a comprehensive complete S1 gene analysis and pathological investigation of the CK/CH/WJ/215 isolate. The results revealed significant genetic differences compared to commonly used vaccine strains, novel glycosylation sites, and a strong multiorgan infective capability. These findings are crucial for understanding the